Domestic Tourism in Indonesia: Another Story of Inequality between Java and Non-Java - Wini Widiastuti (Journal of Indonesian Tourism and Development Studies, 2020)
This study aimed to examine the pattern of movement of domestic tourists within one country, in this case, in Indonesia. Although many scholars had been addressed by tourism in their research, both international and domestic tourism, there was a limited study that examined the spatial pattern of domestic tourism, especially in developing countries. Therefore, this study intended to do so. This study employed a descriptive analysis of the new data set gathered from the Study of Domestic Tourism Market 2017. The result of this study showed that, although visitors can travel either inside one province or to many other provinces in Indonesia, however, the majority of visitors prefer to travel within one province, which might be related to several factors such as cost and transportation facilities. The data also showed evidence of inequality, especially when comparing Java and Non-Java Provinces. One of the reasons for those disparities can be explained by the fact that people living in Java tend to travel only to other provinces around Java Islands. Another reason is that the level of economic development differs from Java and the outer islands. Transportation access has also affected the disparities since all provinces in Java get benefited from the sophisticated and interconnected transportation systems. On the contrary, Non-Java Provinces are hindered by the limited access to transportation modes or by the expensive transportation cost. A big difference in the average income per capita between Java and Non-Java residents also contributed to the inequality in the number of tourists among the provinces. The individual with high income, of course, has more opportunity to do traveling to many places and to visit attractive sites.Keywords: developing country, domestic tourism, economic development, regional disparities.